Accessing Young Children's Ideas about Energy - Franziska Detken; Maja Brückmann (MDPI AG, 2021)
We present a multi-method design for elucidating young, mostly illiterate children's (grades 1 and 2 of Swiss elementary school, ages 6-8) ideas about energy. The design uses semi-structured interviews and video recordings as the main methods of data generation and collection, respectively. A plurality of tasks, including drawing, sorting and a newly developed picture stories task, target core aspects of the scientific energy concept in selected contexts. These tasks provide various opportunities for the children to connect to their prior experiences and express ideas verbally and non-verbally in age-adequate ways, e.g., by gestures or drawings. We illustrate the level of detail and complexity of the children's responses and show how these reflect the children's associations with energy and their patterns of argumentation. These rich data enable analysis regarding various aspects of the scientific energy concept, including sources, users, forms, and the transfer of energy, and the identification of possible starting points for early energy instruction.